Towards Cross-Reality Interaction and Collaboration: A Comparative Study of Object Selection and Manipulation in Reality and Virtuality - Zhang, Shuhao; Li, Yue; Man, Ka Lok; Yue, Yong; Smith, Jeremy (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
Cross-Reality (CR) is an important topic for the research of multiuser collaborative systems. It allows users to participate in the reality-virtuality continuum and select appropriate interactive systems to work with, such as Virtual Reality Head-Mounted Displays (VR HMDs). However, there is limited work showing how interaction in VR differs from the more commonly used Personal Computers (PCs) and tablet devices in terms of object selection and manipulation. In this paper, we present a comparative study that investigated how users perform and perceive workload on 3D object selection and manipulation tasks using different devices (e.g. PC, tablet, and VR). We recorded the time and accuracy as objective task performance measures, and users' self-reported workload as a subjective measure. Our results revealed that unlike the biased performances of PC and tablet, VR has a balanced performance and great potentials in complex tasks.